Produksi Protein Sel Tunggal dari Aspergillus niger Kultur dengan Kulit Nanas (Ananas comosus L. MERR) Media Limbah - Yuli Apriani Br.Lubis; Yayuk Putri Rahayu; Gabena Indrayani Dalimunthe; Haris Munandar Nasution (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Introduction: Single Cell Protein (SCP) is a term used for proteins produced from microbes such as bacteria, algae, yeasts, and fungi. One of the fungi known to produce PST is Aspergillus niger. Objective: The purpose of this study was to determine whether pineapple peel waste could produce single cell protein from A. niger culture and to determine differences in protein production with the addition of nutrients in the fermentation medium. Methods: This research method is an experimental method with the independent variables being MFKN1 medium (Pineapple Skin Fermentation Medium with the addition of KH2PO4 and sugar), and MFKN2 medium (Pineapple Skin Fermentation Medium with the addition of KH2PO4, (NH4)2SO4 and sugar); and the length of fermentation time used are days-0, 2, 4, and 6. The dependent variables of this study were analysis of protein content, dry weight of cells, glucose levels, pH and temperature. The data from this study were statistically analyzed using the two way Anova method. Results: The results of this study obtained the highest protein content in MFKN2 media, namely 0.80% (day-2); cell dry weight 0.473 g; glucose level 1.3406%; pH 4.6 and temperature 31 oC. Meanwhile, the highest protein content in MFKN1 media was 0.59% (day- 4); cell dry weight 0.346 g; glucose level 1.3406%; pH 3.7 and temperature 26.6 oC. Conclusion: The conclusion of this study is that pineapple peel waste can produce single cell protein from A. niger culture and there are differences in protein production results with the addition of nutrients, where protein content in MFKN2 medium is higher than protein content in MFKN1 medium.